A Juridical Demarcation: Reconstructing the Proof of Mens Rea to Differentiate Policy and Corruption by Public Officials - Sutopo, R. Bayu Probo; Panjaitan, Hulman (SIGn Jurnal Hukum, 2025)
The enforcement of anti-corruption law in Indonesia confronts a fundamental paradox. The vigorous campaign to eradicate corruption often results in an erosion of legal certainty and an increased risk of policy criminalization. This issue stems from the distortion and inconsistent application of the principle of a guilty mind (mens rea), as judicial practice frequently equates state financial loss or procedural errors with malicious intent. This research aims to reconstruct the principle of proving mens rea by proposing a clear and operational demarcation framework. Using a normative legal research method that integrates the statute, conceptual, and case study approaches, this study analyzes data through systematic and teleological interpretation, culminating in deductive reasoning. The findings indicate that jurisprudence empirically confirms a dangerous blurring of these concepts. As a solution, this study formulates a framework that strictly differentiates among administrative error, policy error, and intentional corruption. The fundamental line of demarcation among these categories is the presence of a valid and convincingly proven mens rea, defined as the intent to enrich oneself or others unlawfully. The primary contribution of this study is to provide a juridical parameter to enhance legal certainty and protect the legitimate discretionary space of public officials. Ultimately, this framework aims to restore criminal law to its function as a last resort (ultimum remedium), thereby making the fight against corruption more targeted, just, and legitimate.